Hydropic ear disease—Translation of imaging into clinical practice: Clinical image case. Issue 1 (27th February 2018) - Gürkov, Robert; Kalla, Roger; Maxwell, Rebecca; Patzig, Maximilian
A 45-year-old man presented to the neurotology clinic, suffering from recurrent attacks of vertigo associated with falls, of unknown origin. Pure tone audiometry revealed a profound right-sided and mild left-sided pantonal sensorineural hearing loss. Caloric videonystagmography showed marked canal paresis on the right side. Video-head impulse test, however, showed bilaterally normal gain. Cranial magnetic resonance imaging (MRI) was normal. No neurovascular compression was noted. We performed locally enhanced inner ear MRI (LEIM). LEIM revealed a marked dilation of the endolymphatic space of the right inner ear, that is, endolymphatic hydrops. In light of the history, clinical, functional and imaging results, therefore, the diagnosis of hydropic ear disease (Menière's disease) with vestibular drop attacks could be established. This clinical image case illustrates the usefulness of inner ear imaging for the differential diagnosis of vertigo disorders, such as hydropic ear disease (Menière's disease).